Exercise habits and factors associated with exercise in systemic sclerosis: a Scleroderma Patient-centered Intervention Network (SPIN) cohort study. Issue 17 (14th August 2018) - Azar, Marleine; Rice, Danielle B.; Kwakkenbos, Linda; Carrier, Marie-Eve; Shrier, Ian; Bartlett, Susan J.; Hudson, Marie; Mouthon, Luc; Poiraudeau, Serge; van den Ende, Cornelia H. M.; Johnson, Sindhu R.; Rodriguez Reyna, Tatiana Sofia; et al.
Abstract: Objective: Exercise is associated with improved health in many medical conditions. Little is known about the exercise habits of people with systemic sclerosis (SSc, or scleroderma). This study assessed the proportion of individuals with SSc who exercise and associations of demographic and disease variables with exercise. Additionally, the weekly amount of time spent exercising and the types of exercise performed were assessed among patients exercising. Methods: The sample consisted of adult participants with SSc enrolled in the Scleroderma Patient-centered Intervention Network (SPIN) Cohort who completed baseline questionnaires from March 2014 through August 2015. Baseline questionnaires included questions on exercise habits, physician-reported medical characteristics, self-report demographic characteristics, the Health Assessment Questionnaire-Disability Index, Patient Health Questionnaire-9, and Patient-Reported Outcomes Measurement Information System-29. Results: Of 752 patients, 389 (51.7%) reported presently engaging in exercise, and these patients exercised on average 4.7 h [standard deviation (SD) = 2.8] per week. Among patients who reported exercising, walking was most commonly reported ( n  = 295, 75.8%). In bivariate analyses, present exercise was associated with more education, lower body mass index, some (versus no) alcohol consumption, non-smoking, limited/sine disease subtype, absence of skin thickening, lower disability, higher physical function, lower symptoms of anxiety and depression, less fatigue, lower sleep disturbance, higher ability to participate in social roles and activities, and less pain. Conclusions: Approximately half of SSc patients reported that they are currently exercising with walking being the most common form of exercise. Understanding exercise patterns and factors associated with exercise will help better inform intervention programs to support exercise for patients with SSc. Implications for rehabilitation: Systemic sclerosis is a rare autoimmune rheumatic disease associated with great morbidity and highly diverse presentation. Approximately half of people with both limited and diffuse systemic sclerosis report exercising. Most exercisers walk, but patients engage in a wide variety of exercise-related activities. Individually designed exercise programs are most likely to support and encourage exercise in patients with diverse disease manifestations.